2021
DOI: 10.1002/hep.32083
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mitochondrial SAB Deletion or Knockdown Alleviates Diet‐Induced Metabolic Syndrome, Steatohepatitis, and Hepatic Fibrosis

Abstract: Background and Aims The hepatic mitogen‐activated protein kinase (MAPK) cascade leading to c‐Jun N‐terminal kinase (JNK) activation has been implicated in the pathogenesis of nonalcoholic fatty liver (NAFL)/NASH. In acute hepatotoxicity, we previously identified a pivotal role for mitochondrial SH3BP5 (SAB; SH3 homology associated BTK binding protein) as a target of JNK, which sustains its activation through promotion of reactive oxygen species production. Therefore, we assessed the role of hepatic SAB in expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The loss of RINT1 affects the fate of PDAC cells by interfering with the SUMOylation pathway, and in acute liver toxicity [41,42]. In acute hepatotoxicity, mitochondrial SH3BP5, as the target of JNK, maintains its activation by promoting the production of reactive oxygen species [43]. The overexpression of Slc43a3 reduces FA uptake in differentiated OP9 cells and leads to reduced lipid droplet accumulation [44].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of RINT1 affects the fate of PDAC cells by interfering with the SUMOylation pathway, and in acute liver toxicity [41,42]. In acute hepatotoxicity, mitochondrial SH3BP5, as the target of JNK, maintains its activation by promoting the production of reactive oxygen species [43]. The overexpression of Slc43a3 reduces FA uptake in differentiated OP9 cells and leads to reduced lipid droplet accumulation [44].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, JNK targeted GCLC are ubiquitinated and degraded leading to decreased GSH level and increased oxidative stress as occur in the acute acetaminophen hepatotoxicity [ 64 , 77 ]. In NASH, P-JNK targeting of transcriptional factors, such as SREBFs to increase lipogenesis and cholesterol synthesis, NCoR1 to repress PPARα and fatty acid oxidation, leads to cumulative lipotoxic stress [ 78 , 79 , 80 ]. Therefore, P-JNK-SAB ROS activation loop is a key mediator in sustained activation of JNK.…”
Section: Hepatic Mapk Family In Metabolic Stress and The Mechanism Of...mentioning
confidence: 99%
“…Hepatic fat is mostly triglyceride formed by esterification of free fatty acid from the diet, adipose tissue lipolysis and de novo lipogenesis. Fat accumulation in hepatocytes causes lipotoxicity and apoptosis [ 6 , 16 , 53 ] and ballooning degeneration of hepatocytes which are associated with oxidative stress in steatosis/steatohepatitis [ 78 ]. In the course of disease progression, high calorie diet increases mitochondrial function and metabolism accompanied with stress kinase activation [ 78 , 81 ].…”
Section: Hepatic Mapk Mediates Progression Of Nafl/nashmentioning
confidence: 99%
“…JNK-induced SAB phosphorylation promotes mitochondrial dysfunction and ROS production and, as a feedback reaction, it activates the upstream mitogen-activated protein kinase (MAPK) pathway, which is the initial event in the P-JNK-mitoSAB-ROS activation loop [ 126 , 127 , 128 ]. In addition, studies in mice fed by high-fat, high calorie and high-fructose (HFHC) diet demonstrated a time-dependent increase in SAB expression, with the concomitant JNK activation [ 129 ]. The same authors also demonstrated that inducible hepatocyte specific SAB deletion (Sabi∆Hep) in mice reduced significantly the JNK activation after 8 weeks of HFHC diet, accompanied by decreased body fat after 16 weeks.…”
Section: Drugs Inducing Hepatic Steatosismentioning
confidence: 99%
“…Similar data were obtained in 40-week-HFHC fed mice treated with SAB N-acetylgalactosamine antisense oligonucleotide (GalNAc-Sab-ASO) to obtain SAB knockdown mice. SAB knockdown mice, after 40 to 52 weeks of HFHC diet, showed a decreased steatohepatitis and fibrosis and restored SAB and P-JNK levels, with respect to those found in mice fed by standard diet, demonstrating the crucial role of P-JNK-mitoSAB-ROS loop in NASH [ 129 ].…”
Section: Drugs Inducing Hepatic Steatosismentioning
confidence: 99%